An Overview of Vaccination Strategies and Antigen Delivery Systems for Streptococcus agalactiae Vaccines in Nile Tilapia (Oreochromis niloticus) - Munang’andu, Hetron Mweemba (Vaccines (Basel), 2016)
Streptococcus agalactiae is an emerging infectious disease adversely affecting Nile tilapia (Niloticus oreochromis) production in aquaculture. Research carried out in the last decade has focused on developing protective vaccines using different strategies, although no review has been carried out to evaluate the efficacy of these strategies. The purpose of this review is to provide a synopsis of vaccination strategies and antigen delivery systems currently used for S. agalactiae vaccines in tilapia. Furthermore, as shown herein, current vaccine designs include the use of replicative antigen delivery systems, such as attenuated virulent strains, heterologous vectors and DNA vaccines, while non-replicative vaccines include the inactivated whole cell (IWC) and subunit vaccines encoding different S. agalactiae immunogenic proteins. Intraperitoneal vaccination is the most widely used immunization strategy, although immersion, spray and oral vaccines have also been tried with variable success. Vaccine efficacy is mostly evaluated by use of the intraperitoneal challenge model aimed at evaluating the relative percent survival (RPS) of vaccinated fish. The major limitation with this approach is that it lacks the ability to elucidate the mechanism of vaccine protection at portals of bacterial entry in mucosal organs and prevention of pathology in target organs. Despite this, indications are that the correlates of vaccine protection can be established based on antibody responses and antigen dose, although these parameters require optimization before they can become an integral part of routine vaccine production. Nevertheless, this review shows that different approaches can be used to produce protective vaccines against S. agalactiae in tilapia although there is a need to optimize the measures of vaccine efficacy.